MicroRNA-mediated drug resistance in ovarian cancer - Mihanfar, Aynaz; Fattahi, Amir; Nejabati, Hamid Reza (Journal of Cellular Physiology, 2019)
The development of intrinsic or acquired resistance to chemotherapeutic agents used in the treatment of various human cancers is a major obstacle for the successful abolishment of cancer. The accumulated efforts in the understanding the exact mechanisms of development of multidrug resistance (MDR) have led to the introduction of several unique and common mechanisms. Recent studies demonstrate the regulatory role of small noncoding RNA or miRNA in the several parts of cancer biology. Practically all aspects of cell physiology under normal and disease conditions are reported to be controlled by miRNAs. In this review, we discuss how the miRNA profile is changed upon MDR development and the pivotal regulatory role played by miRNAs in overcoming resistance to chemotherapeutic agents. It is hoped that further studies will support the use of these differentially expressed miRNAs as prognostic and predictive markers, as well as novel therapeutic targets to overcome resistance in ovarian cancer.
CRIS-Team WoS Importer:2019-02-22